High Glucose Level Disturbs the Resveratrol-Evoked Curtailment of CX3CL1/CX3CR1 Signaling in Human Placental Circulation. (1st June 2017) - Szukiewicz, Dariusz; Pyzlak, Michal; Szewczyk, Grzegorz; Stangret, Aleksandra; Trojanowski, Seweryn; Bachanek, Michal; Braksator, Wojciech; Wejman, Jaroslaw
Abstract : Hyperglycemia-induced hyperactivity of chemokine CX3CL1 (fractalkine) occurs in the human placenta. Anti-inflammatory/antioxidant activities of resveratrol (3, 5, 4′-trihydroxy- trans -stilbene) are related to the modulation of chemokine CX3CL1 and its receptor, CX3CR1, signaling pathways. We examined the influence of high glucose (25 mmol/L glucose; HG group;N = 36 ) on resveratrol-mediated effects on CX3CL1 and TNF- α production by the placental lobule, CX3CR1 expression and contents of CX3CR1, TNF- α receptor 1 (TNFR1), and NF- κ B proteins in placental tissue. The placental lobules perfused under normoglycemic conditions formed the control NG group (N = 36 ). Resveratrol (50 and 100  μ M; subgroups B and C) administered into the perfusion fluid lowered the production of both CX3CL1 and TNF- α . The reductions in CX3CL1 levels were more evident in the NG group. CX3CR1 expression was significantly higher in the NG subgroups B and C compared to the HG subgroups B and C (385.2 and 426.5% versus 199.3 and 282.4%, resp.). An increase in CX3CR1 protein content in placental lysates was observed in the NG subgroups B and C. Also, resveratrol significantly decreased NF- κ Bp65 protein content only in the NG group, not affecting hyperglycemia-elicited TNFR1 upregulation. In conclusion, euglycemia assures optimal effects of resveratrol pertaining to CX3CL1/CX3CR1 signaling in the placenta. Future studies on resveratrol are needed, especially those including maternal-fetal risk assessments.